Genitourinary Imaging A Case Based Approach - Harisinghani, Mukesh G.; Rajesh, Arumugam (Springer London : Imprint: Springer, 2015)
Covering all modalities currently used as well as emerging novel imaging tools, each chapter covers an aspect of Genitourinary Imaging with a comprehensive coverage of subspeciatlies. Genitourinary Imaging - A Case Based Approach closely mimics day to day clinical practice, and allows retention of  pertinent practice information in an easy to understand format. Providing Genitourinary specific content in a portable form that can be used in close proximity to the PACS workstation, Genitourinary Imaging - A Case Based Approach is the perfect book for residents both in training and practicing as well as genitourinary radiologists worldwide.